PENGGUNAAN SOFTWARE VISSIM UNTUK ANALISIS SIMPANG BERSINYAL (STUDI KASUS SIMPANG MIROTA KAMPUS TERBAN YOGYAKARTA) - Aryandi, Rama Dwi; Munawar, Ahmad (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Traffic jam is one of the main problems nowadays in transportation network, especially in the intersection, because of the conflict of movements between vehicles which came from each of its arms. An intersection is the junction in transportation network where two or more roads either meeting or crossing. In this analysis, author used a traffic simulation with Vissim software to predict the queues. The results have been compared to actual result at the site. Primary data were collected by conducting a survey using traffic counting method on Wednesday afternoon peak hour. The results of both analysis and survey are, average queue length of Vissim is 62 m and average queue length of observation is 60 m. It is concluded that there is no significant different between the simulation and the actual results. However, there is a significant different in deviation of the results.